PERSEPSI PESERTA DIDIK TERHADAP PEMBELAJARAN BIOLOGI TERINTEGRASI NILAI-NILAI ISLAM DI FASE E MAN SE-KOTA PADANG - Husna, Misrayatul; Ardi, Ardi (Jurnal Biogenerasi, 2024)
Students' perceptions of learning can be taken into consideration by teachers and schools to plan better learning in the future. Until now, there has been no research that reveals the integration of Islamic values ​​in biology subjects in MAN in the city of Padang, so researchers are interested in conducting research related to student perceptions. The population in this research is MAN stage E students in the city of Padang. The research sample consisted of 250 students who had implemented integrated biology learning with Islamic values. Sampling using techniques simple random sampling. The data analysis technique used is descriptive percentage analysis. The results of the research show that the perceptions of MAN Padang City students towards integrated biology learning with Islamic values ​​at MAN throughout Padang City are divided into 3 categories, namely quite good, good and very good. Most students' perceptions are in the good category with a percentage of 64.8%. As many as 32.8% of students were in the very good category, and another 2.4% had a perception in the quite good category.